Neuro-Ophthalmology at a Tertiary Eye Care Centre in India. Issue 3 (September 2018) - Dhiman, Rebika; Singh, Digvijay; Gantayala, Shiva P.; Ganesan, Vaitheeswaran L.; Sharma, Pradeep; Saxena, Rohit
Abstract : Background: Neuro-ophthalmology as a specialty is underdeveloped in India. The aim of our study was to determine the spectrum and profile of patients presenting to a tertiary eye care center with neuro-ophthalmic disorders. Methods: A retrospective hospital-based study was conducted, and records of all patients seen at the neuro-ophthalmology clinic of Dr. Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi, India, over a 1-year period were retrieved and evaluated. Results: Of a total of 30, 111 patients referred to various specialty clinics in a span of 1 year, 1597 (5%) were referred for neuro-ophthalmology evaluation. The mean patient age was 30.8 ± 19.5 years, with a male dominance (M:F = 2.02:1). Among these patients, optic nerve disorders were noted in 63.8% (n = 1, 020), cranial nerve palsy in 7% (n = 114), cortical visual impairment in 6.5% (n = 105), and others (eye/optic nerve hypophasia, blepharospasm, and optic disc drusen) in 6% (n = 95). Among the patients with optic nerve disorders, optic neuropathy without disc edema/(traumatic optic neuropathy, hereditary, tumor-related, retrobulbar neuritis, toxic, and idiopathic) was noted in 42.8% (n = 685) and optic neuropathy with disc edema (ischemic optic neuropathy, papilledema, post-papilledema optic atrophy, papillitis, neuroretinitis, and inflammatory optic neuropathy) in 20.9% (n = 335). Sixteen percent of patients (n = 263) were incorrect referrals. Conclusion: The neuro-ophthalmic clinic constitutes a significant referral unit in a tertiary eye care center in India. Traumatic and ischemic optic neuropathies are the most common diagnoses. Neuro-ophthalmology requires further development as a subspecialty in India to better serve the nation's population.